2019
DOI: 10.1891/2380-9418.12.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Teaching It Forward: Educating Parents About HPV/HPV Vaccine

Abstract: BackgroundHuman papillomavirus (HPV) vaccines are available to prevent HPV-associated cancers. However, parents are reluctant to make the decision to immunize their children. Nationally, HPV vaccination rates remain low.ObjectiveThe objectives were to improve parents' attitudes and knowledge about HPV/HPV vaccine, increase parental intent to vaccinate, and increase HPV vaccination rates in a primary care office.MethodsA one-group, pretest/posttest design was used to assess participants' attitude, knowledge, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…As Sitaresmi M.N. et al proved, there was a significant correlation between increasing HPV vaccine acceptability with the improvement of awareness, knowledge, perception toward HPV infection, cervical cancer and HPV vaccination (r = 0.32 to 0.53, p<0.001) and other numerous studies have confirmed, and we can see from valuable motives in our study, it is very important to educate parents and distribute important facts about the benefits of this vaccine and the HPV prevention [32][33][34]. Consequently, in this way, educated parents with sufficient knowledge will be empowered enough to ask for vaccination of their child(ren) even without a "paediatrician's recommendation".…”
Section: Plos Onesupporting
confidence: 76%
“…As Sitaresmi M.N. et al proved, there was a significant correlation between increasing HPV vaccine acceptability with the improvement of awareness, knowledge, perception toward HPV infection, cervical cancer and HPV vaccination (r = 0.32 to 0.53, p<0.001) and other numerous studies have confirmed, and we can see from valuable motives in our study, it is very important to educate parents and distribute important facts about the benefits of this vaccine and the HPV prevention [32][33][34]. Consequently, in this way, educated parents with sufficient knowledge will be empowered enough to ask for vaccination of their child(ren) even without a "paediatrician's recommendation".…”
Section: Plos Onesupporting
confidence: 76%
“…Evidence for system-, provider-and parent-targeted strategies to mitigate these barriers has been established. Strategies include system-level changes to electronic health records to routinize provider prompts to recommend HPV vaccination and audit and feedback strategies [22], provider-level interventions to promote effective provider communication (including presumptive, bundled, and/or unqualified provider recommendations) [23], and patient reminders [24] and parent education [25] aimed at parent determinants. There is also modest evidence for the implementation of parent-and patient-focused apps to promote HPV education and vaccination [26][27][28].…”
Section: Introductionmentioning
confidence: 99%